A new fossil lacewing genus from the Middle Jurassic of Inner Mongolia, China (Neuroptera: Osmylidae) - Wang, Yongjie; Liu, Zhiqi; Ren, Dong (Zootaxa, 2009)
Fossil Osmylidae showed most diversity in the Old World (Grimaldi and Engel 2005), and many new taxa have been erected (Carpenter 1943, Panfilov 1980, Lambkin 1988, Markakin 1990, Ponomarenko 2003, Ren and Yin 2002, Ren and Engel 2007, Menon and Makarkin 2008), which greatly advanced the understanding and knowledge of osmylid palaeodiversity. However, most were merely founded as new taxa without clarifying their status in Osmylidae. Spilosmylinae (Krüger, 1913), an extant subfamily, is the largest group of Osmylidae containing about 100 recent species, which is comprised of Thyridosmylus Krüger, 1913, Thaumatosmylus Krüger, 1913, Lysmus Navás, 1911, Spilosmylus Kolbe, 1897 and Glenosmylus Krüger, 1913. The subfamily is characterized by the following fetures: moderate body side; simple costal cross-veins; numerous cross-veins in radial sector; MP forked close to the base of wing, which is also general occurrence in the fossil osmylids. However, up to now there were no related fossil taxa to be assigned to Spilosmylinae. We consider there should be more fossil osmylids which have the close affiliation with Spilosmylinae.